2022
DOI: 10.1177/20406223211063039
|View full text |Cite
|
Sign up to set email alerts
|

One-year outcomes and predictive factors for primary patency after stent placement for treatment of central venous occlusive disease in hemodialysis patients

Abstract: Objective: The study purpose was to determine the outcomes and factors predictive of primary stent patency for the treatment of central venous occlusive disease (CVOD) in hemodialysis patients. Methods: Data of 71 patients with CVOD treated with stent placement from January 2012 to December 2017 were analyzed. Univariate and multivariate analysis was performed to determine factors associated with stent patency. Adverse events related to stent placement were also examined. Results: The median primary patency du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Table 2 lists a few studies that reported data on the safety and effectiveness of CS. Furthermore, a study by Chen et al ( 27 ) reported that the use of CS (Viabahn ® , W. L. Gore & Associates Inc., Flagstaff, AZ, USA) was an independent predictor for better primary patency rates. The CS favorable outcomes can be attributed to the inherent mechanism of prohibiting in-stent intimal hyperplasia formation via the covered design, thus, reducing the need for additional patency maintaining interventions vis-à-vis the BMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 lists a few studies that reported data on the safety and effectiveness of CS. Furthermore, a study by Chen et al ( 27 ) reported that the use of CS (Viabahn ® , W. L. Gore & Associates Inc., Flagstaff, AZ, USA) was an independent predictor for better primary patency rates. The CS favorable outcomes can be attributed to the inherent mechanism of prohibiting in-stent intimal hyperplasia formation via the covered design, thus, reducing the need for additional patency maintaining interventions vis-à-vis the BMS.…”
Section: Discussionmentioning
confidence: 99%
“…Boutrous et al ( 26 ) showed that a longer stent is associated with decreased patency rates (62.5 vs. 50 centimeters; P=0.002). In another study, larger vessel diameters (i.e., >12 mm) had higher primary patency rates as stents with larger diameters were used ( 27 ). Based on our previous experiences, for isolated innominate lesions, we would use either Bard Fluency Plus (BD Interventional, Franklin Lakes, NJ, USA) or Atrium iCAST (Hudson, NH, USA), both of which provide a benefit of accuracy for device deployment.…”
Section: Discussionmentioning
confidence: 99%
“…The classic description is mostly in younger population and can present with venous thrombosis or intermittent symptomatic obstruction. Compression of neurologic structures is most common with a relative incidence of 80%, followed by venous (19%) and arterial (2%) [1]. Although the same anatomic predisposition can exist in dialysis patients, there is an added feature that is not present in the classic VTOS patients; namely the increased flow (venous return) from the upper extremity because of the HD acces which dilates the venous structures.…”
Section: Introductionmentioning
confidence: 99%
“…This subclavian venous occlusive disease poses a continuing and significant burden to patients undergoing long-term hemodialysis, causing ipsilateral limb swelling, and potentially access dysfunction related to venous hypertension. 1 The incidence of this VTOS like condition in hemodialysis patients has been increasing, so efficient management of this condition is essential [1]. Dialysis-related central stenosis can be due to multiple contributing factors, including catheter placement, venous flow, and compressive anatomy, leading to upper extremity HD access dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation